Development of Ultralow Interfacial Tension Lignosulfonate from Kraft Black Liquor for Enhanced Oil Recovery - Muhammad Mufti Azis; Fergie Febrina; Ignesti Anindia; Galuh Almas Darmawati; Desi Amalia Fenyka; Suryo Purwono; Rochmadi Rochmadi (Journal of Engineering and Technological Sciences, 2021)
Indonesia aims to implement large-scale enhanced oil recovery (EOR) to increase the national oil production. Chemical EOR is a promising technology to boost the production of old reservoirs with the aid of surfactants and polymers. Thus, the production of low-cost EOR surfactants from local resources with acceptable performance is highly attractive. The objective of the present work was to demonstrate the development of low-cost lignosulfonate surfactant production from kraft black liquor (BL). First, lignin was isolated from black liquor using a novel CO2 bubbling technique, followed by addition of coagulants. Next, sodium lignosulfonate (SLS) was synthesized from the resulting lignin, followed by formulation of SLS with octanol and palm fatty acid distillate (PFAD) soap to obtain an ultralow interfacial tension (IFT) surfactant. The initial IFT value of the SLS solution was already high at 0.7 mN/m. After formulation, the composition SLS:PFAD soap:octanol = 70:22:8 (wt%) improved the IFT value to 3.1 10-3 mN/m. An ultralow IFT in the range of 10-3 mN/m as achieved here fulfills the required IFT value for EOR surfactant.